2019
DOI: 10.4209/aaqr.2018.08.0284
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Particulate Pollution Measured in Bangladesh from 2014 to 2017

Abstract: Recently, the World Health Organization ranked Narayanganj, Chittagong, and Dhaka among the top 25, 40, and 45 cities, respectively, for high ambient PM 2.5 concentrations. Bangladesh has instituted an air quality monitoring system operated by the Department of Environment. PM 2.5 and PM 10 were measured hourly from January 2014 through December 2017 in Dhaka, Gazipur, Narayanganj, Chittagong, Sylhet, and Barisal. All sites registered concentrations for both pollutants that exceeded the 24-h Bangladesh Nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…The positive association of PM with the North-South component of wind speed (CosWD) suggests that PM2.5 concentrations increase when winds come from north directions. This finding is in the line with earlier literature (M. M Mahmood et al, 2019). where winds coming from north-west direction…”
supporting
confidence: 94%
See 2 more Smart Citations
“…The positive association of PM with the North-South component of wind speed (CosWD) suggests that PM2.5 concentrations increase when winds come from north directions. This finding is in the line with earlier literature (M. M Mahmood et al, 2019). where winds coming from north-west direction…”
supporting
confidence: 94%
“…Although studies have shown that wind coming from the northwest direction of Dhaka during the winter months increases PM concentration Mahmood et al, 2019), wind direction was not included as a predictor in the multilinear regression or correlation analysis in the above-mentioned studies.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the conventional brick kilns adjacent to the city, vehicles, uncontrolled development activities, stockpiling of uncovered construction materials along with roadside, and the biomass burning in industries in and around the city are considered as the catalysts behind such unhealthy air [25][26][27][28]. However, the pollution level varies depending on the climatic condition.…”
Section: Introductionmentioning
confidence: 99%
“…However, the pollution level varies depending on the climatic condition. The brick kilns operating during the dry seasons [29,30] contribute about % of the total PM pollution of the city [26,28,31], resulting in higher particulate pollution concentration during this time. Moreover, the low particle deposition rate at dry season facilitates higher pollution levels during this period than the wet season [28,32].…”
Section: Introductionmentioning
confidence: 99%